Public Corruption and Organizational Performance: Evidence from Highway Transportation - Liu, Cheol; Chen, Can; Lee, Jekyung (KDI School of Public Policy and Management, 2020)
Public corruption has significant negative effects on the performance of public agencies in both developing and developed countries. In this paper, we propose a theoretical approach to understanding the potential impact of public corruption on the performance of public organizations. We constructed multiple indexes for capturing the sectoral and overall performance of US state highway transportation agencies based on road quality, the status of bridges, traffic congestion, traffic fatalities, and overall highway performance. Using state panel data for the period from 2002 to 2008, we found that public corruption had a negative impact on the quality of state roads and bridges and on traffic congestion and was associated with increases in traffic fatalities. Overall, we confirmed that corruption has the potential to diminish significantly the performance of US highway transportation agencies.
Keywords: Corruption; Infrastructure; Organizational Performance; Transportation Agencies